Alpha-1 antitrypsin deficiency alleles and severe cystic fibrosis lung disease. Issue 12 (1st December 1998) - Mahadeva, R; Stewart, S; Bilton, D; Lomas, D A
Abstract : BACKGROUND: Alpha-1 antitrypsin (α1 -AT) is the most abundant proteinase inhibitor within the lung. We have recently reported the surprising observation that cystic fibrosis patients with mild to moderate deficiency of α1 -antitrypsin have significantly better pulmonary function than non-deficient patients. This study may have been biased as it did not include the most severely affected patients who have died in childhood or those who have undergone orthotopic lung transplantation. The prevalence of α1 -antitrypsin deficiency alleles in this most severely affected group of patients with cystic fibrosis was therefore assessed. METHODS: DNA was obtained from neonatal blood spots from children with cystic fibrosis who had died from pulmonary disease and from formalin fixed lung tissue from transplanted cystic fibrosis patients. The common S and Z deficiency alleles of α1 -AT were sought by amplification mutagenesis of the appropriate region of the α1 -AT gene followed by restriction enzyme digestion with Xmn I and Taq I, respectively. RESULTS: Seventy nine patients were identified (seven dead, 72 transplanted). Two patients (2.5%) were heterozygous for the Z allele of α1 -AT and four (5.1%) were heterozygous for the S allele. This is not significantly different from the incidence in the normal population of 4% and 8% for the S and Z alleles, respectively. CONCLUSIONS: These data support previous findings that deficiency of α1 -AT is not associated with more severe pulmonary disease in cystic fibrosis and may be associated with milder lung disease. Further work is needed to clarify the mechanisms underlying the progressive lung damage in cystic fibrosis.